2012
DOI: 10.1080/1070289x.2012.672838
|View full text |Cite
|
Sign up to set email alerts
|

Beautiful stereotypes: the relationship between physical attractiveness and mixed race identity

Abstract: The idea that mixed race individuals are physically attractive is a commonly accepted stereotype. Past research in which whites (Australians and British) and Asians (Japanese) were asked to rate the attractiveness of a racially heterogeneous group of faces has shown that mixed race phenotype was judged the most attractive. In this study, I examine whether there is empirical evidence for this Biracial Beauty Stereotype in the United States. Using the data from the National Longitudinal Survey of Adolescent Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 31 publications
(38 reference statements)
1
18
0
Order By: Relevance
“…As an innovative, big data source, data retrieved from online dating websites provide researchers an opportunity to newly examine multiraciality from an interactional angle. Multiracial women of White and non-White ancestry have been characterized as "exotic" and "tragic" in the media and popular culture (Beltrán and Fojas 2008;Joseph 2012;Nishime 2014;Osei-Kofi 2013;Sims 2012), and qualitative studies find that this characterization often shapes the encounters mixedrace women have with their monoracial peers, especially in dating (Basu 2010;Romo 2011;Root 2004;Waring 2013). On the one hand, hypodescent (also known as the "one-drop rule") may still reign supreme in a social arena such as politics, where whiteness is pervasive; on the other hand, perceptions of multiraciality may be more dimensionalized in settings with greater racial diversity.…”
Section: Multiraciality In Cyberspace: the Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…As an innovative, big data source, data retrieved from online dating websites provide researchers an opportunity to newly examine multiraciality from an interactional angle. Multiracial women of White and non-White ancestry have been characterized as "exotic" and "tragic" in the media and popular culture (Beltrán and Fojas 2008;Joseph 2012;Nishime 2014;Osei-Kofi 2013;Sims 2012), and qualitative studies find that this characterization often shapes the encounters mixedrace women have with their monoracial peers, especially in dating (Basu 2010;Romo 2011;Root 2004;Waring 2013). On the one hand, hypodescent (also known as the "one-drop rule") may still reign supreme in a social arena such as politics, where whiteness is pervasive; on the other hand, perceptions of multiraciality may be more dimensionalized in settings with greater racial diversity.…”
Section: Multiraciality In Cyberspace: the Contextmentioning
confidence: 99%
“…Studies find evidence for a multiracial desirability rooted in a racial ideology that confers fetishized standards of attractiveness and beauty to perceived gendered racial hybridity (Haritaworn 2007;Root 2004;Waring 2013). Sims's (2012) analysis of Add Health data tested whether a "biracial beauty stereotype" operates among male and female adolescents; she found that interviewers rated multiracial respondents as the most attractive. Sims's (2012) analysis of Add Health data tested whether a "biracial beauty stereotype" operates among male and female adolescents; she found that interviewers rated multiracial respondents as the most attractive.…”
Section: Multiracial Dividend Effectmentioning
confidence: 99%
“…Rhodes et al (2005) report empirical evidence using facial composites that support this stereotype. Sims (2012) found that in mixedparentage groups containing mixed-identified respondents, interviewers rated those respondents as the most attractive of their respective groups, but rated the mixed minority identified as the most attractive of all. Lewis (2010), a Cardiff University psychologist, also sought to test whether people of 'mixed-race' were perceived as being more attractive than non-'mixed-race' people.…”
Section: 'More Attractive…disproportionately Successful'mentioning
confidence: 91%
“…Using data from the 1979-80 the National Survey of Black Americans (NSBA), Hill (2002) found that lighter skin tone was associated to higher ratings of physical attractiveness for black adults and this association was stronger for women than for men. More recently, Sims (2012) and Reece (2016), both using the Add Health data, have demonstrated that the relationship between phenotype and beauty standards holds true for blacks, yet is more complex than has traditionally been thought. Using the concept of "biracial beauty stereotype," that is a belief that biracial people are more attractive than monoracial people, Sims (2012) argued that physical attractiveness, either self-perceived or externally rated, has an effect on one's racial identify.…”
Section: Colorism and Beauty Standardsmentioning
confidence: 99%
“…More recently, Sims (2012) and Reece (2016), both using the Add Health data, have demonstrated that the relationship between phenotype and beauty standards holds true for blacks, yet is more complex than has traditionally been thought. Using the concept of "biracial beauty stereotype," that is a belief that biracial people are more attractive than monoracial people, Sims (2012) argued that physical attractiveness, either self-perceived or externally rated, has an effect on one's racial identify. Although her results were mixed, they held true for people of African descent.…”
Section: Colorism and Beauty Standardsmentioning
confidence: 99%